Congenital isolated bilateral upper lid coloboma - Shrestha, JB; Shrestha, GS; Joshi, N; Karmacharya, PC (Nepalese Journal of Ophthalmology, 2012)
A case of congenital isolated coloboma of both the upper lids from just lateral to the lacrimal punctum up to the medial half, with symblepharon in the region of lower eyelid, was studied in a 7-year-old female child. She did not have any other associated anomalies. The birth and family histories were normal. The puncta were normal in position and well apposed to the globe. The closure of the lid coloboma was done by release of symblepharon along with direct closure of the defect, for the right eye first, and one month later, for the left eye. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5877 NEPJOPH 2012; 4(1): 194-196